An Introduction to the Study of Wisdom Literature. By Stuart Weeks - Dell, Katharine (The journal of theological studies, 2012)
Problems of definition and scope beleaguer the wisdom literature, and this is well expressed in this short guide to the subject. Weeks chooses to begin his discussion with the extra-Israelite literature that bears a family resemblance to Israelite wisdom. The problem here is, however, the circularity that these texts are being brought together artificially because of their resemblance to Israelite wisdom—there was no category of ‘wisdom’ in Egyptian or Mesopotamian circles and one wonders indeed, on close analysis of Weeks’s caution in this guide, if there was even one for Israelite literature. Weeks says towards the end of the book ‘wisdom literature is our category, not one bequeathed to us by the biblical writers themselves’ (p.